KEPUTUSAN PEMBELIAN PRODUK KOSMETIK DAN ISU LINGKUNGAN - Desi Herawati; Suprihatin Ali; Diang Adistya (Jurnal Perspektif Bisnis, 2022)
The environment is becoming an important issue in companies today—not just products but also marketing processes and the company's commitment to actively participate in environmentally friendly campaigns. One of them is in cosmetic products. In particular, this study provides insight into the effect of green products, green advertising, and green trust on purchasing decisions for cosmetic products. The quantitative approach was applied to 100 samples selected purposefully. Multiple linear regression was used to analyze the data. The results of the study partially show that green advertising has a stronger influence than green products. However, there is no effect of green trust on purchasing decisions for cosmetic products. Aspects that are highly valued when choosing environmentally friendly cosmetic products are product safety, protecting the beauty of the earth, and participating in preserving the environment. ABSTRAK Lingkungan menjadi isu penting dalam perusahaan saat ini, tidak hanya sekedar produk, tetapi juga proses pemasaran dan komitmen perusahaan untuk berpartisipasi aktif dalam kampanye ramah lingkungan. Salah satunya pada produk kosmetik. Secara khusus studi ini memberikan wawasan mengenai pengaruh green product, green adverting, dan green trust terhadap keputusan pembelian produk kosmetik. Pendekatan kuantitatif diterapkan terhadap 100 sampel yang dipilih secara purposif. Data dianalisis menggunakan regresi linier berganda. Hasil penelitian secara parsial menunjukkan green advertising memberikan pengaruh yang lebih kuat daripada green product. Walaupun demikian, tidak terdapat pengaruh green trust terhadap keputusan pembelian produk kosmetik. Aspek yang dinilai tinggi untuk memilih produk kosmetik yang ramah lingkungan adalah keamanan produk, menjaga keindahan bumi dan ikut serta melestarikan lingkungan.